High-frequency magnetoimpedance properties in Finemet-type ribbons with a Cu-Co electrodeposited layer - Silveyra, Josefina María (2010)
A comprehensive analysis of magnetoimpedance phenomena in Finemet-type as spun ribbons with a Cu-Co layer electrodeposited at different currents is presented here as a function of microstructure. The measurements were performed in moderate and high frequencies (30 kHz-6 GHz) under an axial magnetic field, up to 25 kA/m. The magnetoimpedance variations have been studied by measuring the reflection parameter S11 of a coaxial line containing the magnetic sample by means of a vector network analyzer. The GMI vs applied field curve does not show a monotonic decay but displays a maximum. GMI first increases with frequencies up to ∼10 MHz reaching values of ΔZ/Zmax ∼ 20%. At higher frequencies the GMI ratio is seen to decrease becoming vanishingly small at ∼1 GHz. © 2009 Elsevier B.V. All rights reserved.